(3RgQI GdQjGV hfRgI GdeQJGVs - (3LeGd GdOjf CMeO GdWGhSj,J (B673 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3GdMeO ddg GdPj ScfJ Edjg bdhH GdYGQajf, hScHJ SMH jOjg ZjGKG ddYGdejf s
(3BNQgG (B:s
(3hgG CfG CNJe gPg GdeYGfj HOYhGJ fLRJ cJGHJg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B620s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje (B- (3GdfLa (B(5/433) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs